2021
DOI: 10.3390/bios11030081
|View full text |Cite
|
Sign up to set email alerts
|

Signal Amplification in an Optical and Dielectric Biosensor Employing Liquid Crystal-Photopolymer Composite as the Sensing Medium

Abstract: An optical and dielectric biosensor based on a liquid crystal (LC)–photopolymer composite was established in this study for the detection and quantitation of bovine serum albumin (BSA). When the nematic LC E7 was doped with 4-wt.% NOA65, a photo-curable prepolymer, and photopolymerized by UV irradiation at 20 mW/cm2 for 300 s, the limit of detection determined by image analysis of the LC optical texture and dielectric spectroscopic measurements was 3400 and 88 pg/mL for BSA, respectively, which were lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…To eliminate the costly and time-consuming p cedure of labeling, a number of label-free approaches aimed at enhancing the optical s nal and thereby improving detection sensitivity at the LC-solid interface of a sandwich LC cell were proposed, which include the use of a highly birefringent LC [38,39] and L photopolymer composite [12], adjustment of the direction of linearly polarized light fo dye-doped LC [16], modification of the alignment layer by ultraviolet light irradiation [ and application of a weak electric field to orient LC molecules in a pre-tilted state [4 Because of the similar working principles between the LC film and LC cell in biodetecti at the LC-glass interface, most of the previously reported signal amplification approach for sandwiched cells would be applicable to the LC film. We have demonstrated that s nal amplification can be achieved with both spin-coated film and sandwiched cell of LC-photopolymer composite [12,31]. In addition, the intensity of the optical response Signal amplification mediated by labeling with gold nanoparticles has been reported in several LC-based biosensors [33][34][35][36][37].…”
Section: Signal Amplification Of Single-substrate Detection Through the Control Of Film Thicknessmentioning
confidence: 99%
See 2 more Smart Citations
“…To eliminate the costly and time-consuming p cedure of labeling, a number of label-free approaches aimed at enhancing the optical s nal and thereby improving detection sensitivity at the LC-solid interface of a sandwich LC cell were proposed, which include the use of a highly birefringent LC [38,39] and L photopolymer composite [12], adjustment of the direction of linearly polarized light fo dye-doped LC [16], modification of the alignment layer by ultraviolet light irradiation [ and application of a weak electric field to orient LC molecules in a pre-tilted state [4 Because of the similar working principles between the LC film and LC cell in biodetecti at the LC-glass interface, most of the previously reported signal amplification approach for sandwiched cells would be applicable to the LC film. We have demonstrated that s nal amplification can be achieved with both spin-coated film and sandwiched cell of LC-photopolymer composite [12,31]. In addition, the intensity of the optical response Signal amplification mediated by labeling with gold nanoparticles has been reported in several LC-based biosensors [33][34][35][36][37].…”
Section: Signal Amplification Of Single-substrate Detection Through the Control Of Film Thicknessmentioning
confidence: 99%
“…Because of the similar working principles between the LC film and LC cell in biodetection at the LC-glass interface, most of the previously reported signal amplification approaches for sandwiched cells would be applicable to the LC film. We have demonstrated that signal amplification can be achieved with both spin-coated film and sandwiched cell of an LC-photopolymer composite [12,31]. In addition, the intensity of the optical response to BSA was enhanced when a 3.4 µm-thick E7 film was spin-coated on DMOAP slides modified with ultraviolet light or when the high-birefringence LC HDN was used instead of E7 to form the sensing LC film, resulting in an improvement in LOD from 10 −8 to 10 −9 g/mL BSA (data not shown).…”
Section: Signal Amplification Of Single-substrate Detection Through the Control Of Film Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic birefringence in LCs enables such interactions to be observed through the change in optical appearance under a polarizing optical microscope (POM) [4][5][6][7][8]. In addition to textural observation, other unique properties of LCs, particularly dielectric anisotropy and electro-optical response, are utilized to establish novel LC-based biosensors for quantitative and signal amplification purposes [5,[9][10][11][12]. For biodetection at the LC-glass interface, dimethyloctadecyl [3-(trimethoxysilyl)propyl] ammonium chloride (DMOAP), a silane coupling reagent, is commonly used to maintain the vertical alignment of LC molecules through its long alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…Using bovine serum albumin (BSA) as the model protein and pristine nematic LCs such as the eutectic mixture E7 as the sensing mesogenic media, the limit of detection (LOD) for LC-based biosensors was reported to be within the order of magnitude of 10 −5 -g/mL BSA [11]. Several strategies have been developed in order to improve the LOD of LC-based detection at the LC-glass interface.…”
Section: Introductionmentioning
confidence: 99%